Ultra-high strength spring wire rod, steel wire and manufacturing method thereof
The development of a wire rod for ultra-high strength springs with a controlled composition and manufacturing process addresses the limitations of existing spring steel materials, achieving high strength and low material deviation, suitable for motorcycle suspension applications.
Patent Information
- Application Number
- JP2023537403
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2020-12-18
- Filing Date
- 2021-11-18
- Publication Date
- 2025-04-22
- Estimated Expiration
- 2041-11-18
AI Technical Summary
Existing spring steel materials used in motorcycle suspensions lack sufficient strength and fatigue resistance, and the application of tempered martensite steel from automobiles is difficult due to manufacturing complexities and high costs.
A wire rod for ultra-high strength springs with a specific composition (C: 0.5-0.7%, Si: 0.4-0.9%, Mn: 0.3-0.8%, Cr: 0.2-0.6%) and manufacturing method involving continuous casting and controlled rolling to minimize segregation, ensuring high strength and low material deviation after IT heat treatment.
The solution provides high-quality ultra-high strength spring wire rods with minimal material deviation after IT heat treatment, achieving high strength and a cross-sectional reduction rate of 40% or more, suitable for applications requiring low spring index.
Smart Images

Figure 0007667279000001 
Figure 0007667279000002 
Figure 0007667279000003
Abstract
Description
[Technical field]
[0001] The present invention relates to ultra-high strength spring wire rod, steel wire, and a manufacturing method thereof, and more particularly, to ultra-high strength spring wire rod, steel wire, and a manufacturing method thereof that can be applied to suspension springs of motorcycles. [Background technology]
[0002] Similar to the automotive materials market, the motorcycle market is also continuously promoting weight reduction and structural changes. Recently, the dual-type suspension used in conventional motorcycles has been replaced by a mono-type, which has increased the demand for high-strength spring steel.
[0003] Conventional spring steel used in motorcycle suspensions is a hard steel wire that does not have enough strength and fatigue resistance to be used in mono-type suspensions. As a result, the use of tempered martensite (TM) steel for automobiles was considered, but there are problems with its application to motorcycle suspension springs, as automotive suspension springs are subject to strict control standards, are difficult to manufacture, and are expensive.
[0004] To solve this problem, there is a method to reduce the alloy content and lower the tempering temperature. However, when the alloy content is reduced and the tempering temperature is lowered, it is difficult to ensure softness with high strength, resulting in a problem of insufficient workability. To solve this problem, segregation control is required to ensure sufficient softness even at a low tempering temperature.
[0005] Recently, with the development of IT heat treatment (Induction heat treatment) technology, sufficient hardening ability can be ensured even when water cooling is used, and the target strength can be achieved while reducing the amount of alloy elements contained in the steel. However, spring steel manufactured through IT heat treatment has a very large deviation in material quality depending on the degree of segregation. In particular, the higher the strength of the steel, the more severe the deviation in material quality due to segregation tends to be. Therefore, when applying IT heat treatment, segregation control is necessary to ensure high strength and a stable reduction in area. [Prior art documents] [Patent documents]
[0006] [Patent Document 1] Korean Patent Publication No. 1995-0018545 Summary of the Invention [Problem to be solved by the invention]
[0007] In order to solve the above-mentioned problems, the present invention provides a high-quality ultra-high strength spring wire rod, steel wire, and a manufacturing method thereof that can ensure high strength and high area reduction rate by reducing material deviation after IT heat treatment. [Means for solving the problem]
[0008] In order to achieve the above object, the present invention provides an ultra-high strength spring wire rod containing, by weight, 0.5-0.7% C, 0.4-0.9% Si, 0.3-0.8% Mn, 0.2-0.6% Cr, 0.015% or less P, 0.010% or less S, 0.01% or less Al, 0.01% or less N, 0.01% or less O, with the balance being Fe and unavoidable impurities, 2 The alloy is characterized in that the ratio of the area that satisfies one or more of C>0.8%, Si>0.9%, Cr>0.8% and Mn>0.8% by weight is 5% or less.
[0009] In the ultra-high strength spring wire rod according to one example of the present invention, the surface ferrite decarburized layer may have a thickness of 1 μm or less.
[0010] In order to achieve the above object, a method for producing an ultra-high strength spring wire rod of the present invention includes a step of continuously casting a molten steel containing, by weight, 0.5-0.7% C, 0.4-0.9% Si, 0.3-0.8% Mn, 0.2-0.6% Cr, 0.015% or less P, 0.010% or less S, 0.01% or less Al, 0.01% or less N, 0.005% or less O, with the balance being Fe and unavoidable impurities, to prepare a bloom, and a step of rolling the bloom into a steel slab and then rolling it into a wire rod, wherein the step of continuously casting includes a casting speed of 0.48-0.54 m / min and soft reduction with a total reduction of 15-35 mm during the continuous casting.
[0011] The manufacturing method of the ultra-high strength spring wire rod of the present invention is characterized in that the soft reduction is performed by rolling at 4 mm or less for each rolling roll, and when the solidification fraction is 0.6 or more, the cumulative reduction amount is 60% or more.
[0012] Further, in order to achieve the above object, an ultra-high strength spring steel wire of the present invention contains, by weight%, 0.5 to 0.7% C, 0.4 to 0.9% Si, 0.3 to 0.8% Mn, 0.2 to 0.6% Cr, 0.015% or less P, 0.010% or less S, 0.01% or less Al, 0.01% or less N, 0.01% or less O, with the balance being Fe and unavoidable impurities, contains 90% or more tempered martensite by area fraction, and has a 1 mm thickness within the center of a cross section perpendicular to the longitudinal direction 2 The alloy is characterized in that the ratio of the area that satisfies one or more of C>0.8%, Si>0.9%, Cr>0.8% and Mn>0.8% by weight is 5% or less.
[0013] The ultra-high strength spring steel wire of the present invention may have a hardness deviation of 25 Hv or less in a cross section perpendicular to the longitudinal direction, in a region excluding a region having a depth of 0.5 mm or less from the outermost surface.
[0014] The ultra-high strength spring steel wire of the present invention may have a tensile strength of 1750 to 2200 MPa and a reduction in area of 40% or more.
[0015] Further, in order to achieve the above object, a method for producing an ultra-high strength spring steel wire of the present invention comprises, by weight%, 0.5-0.7% C, 0.4-0.9% Si, 0.3-0.8% Mn, 0.2-0.6% Cr, 0.015% or less P, 0.010% or less S, 0.01% or less Al, 0.01% or less N, 0.01% or less O, with the balance being Fe and unavoidable impurities, 2 The method includes the steps of drawing a wire rod having an area ratio of 5% or less that satisfies one or more of C>0.8%, Si>0.9%, Cr>0.8% and Mn>0.8% by weight, heating the wire rod to 900-1000°C within 10 seconds, water cooling at high pressure, heating the wire rod to 400-500°C within 10 seconds, tempering the wire, and water cooling the wire. Effect of the Invention
[0016] According to the present invention, it is possible to provide an ultra-high strength spring wire rod, steel wire, and a manufacturing method thereof, which can ensure high strength even with a low alloy content, can ensure excellent area reduction rate by reducing central segregation, and can be applied to products that require a low spring index, as compared with conventional spring steel wires. The present invention can provide a high-quality ultra-high strength spring wire rod, steel wire which has little material deviation after IT heat treatment and can ensure high strength and a high area reduction rate, and a manufacturing method thereof. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0017] As a means for achieving the above object, an ultra-high strength spring wire rod according to one embodiment of the present invention contains, by weight, 0.5-0.7% C, 0.4-0.9% Si, 0.3-0.8% Mn, 0.2-0.6% Cr, 0.015% or less P, 0.010% or less S, 0.01% or less Al, 0.01% or less N, 0.01% or less O, with the balance being Fe and unavoidable impurities, and 2 The ratio of the area that satisfies one or more of C>0.8%, Si>0.9%, Cr>0.8% and Mn>0.8% by weight may be 5% or less.
[0018] In the following, preferred embodiments of the present invention will be described. However, the embodiments of the present invention may be modified into various other forms, and the technical concept of the present invention is not limited to the embodiments described below. Furthermore, the embodiments of the present invention are provided to more completely explain the present invention to those having average knowledge in the art.
[0019] The terms used in this application are merely used to describe specific examples. Therefore, singular expressions include plural expressions unless the context clearly requires singularity. In addition, it should be noted that the terms "include" or "comprise" used in this application are used to clearly indicate the presence of features, steps, functions, components, or combinations thereof described in the specification, and are not used to preliminarily exclude the presence of other features, steps, functions, components, or combinations thereof.
[0020] In addition, unless otherwise defined, all terms used in this specification should be considered to have the same meaning as that generally understood by a person having ordinary knowledge in the technical field to which the present invention belongs. Therefore, unless clearly defined in this specification, a specific term should not be interpreted in an overly ideal or formal sense. For example, in this specification, a singular expression includes a plural expression unless there is a clear exception in the context.
[0021] In addition, in this specification, the terms "about," "substantially," and the like, when given manufacturing and material tolerances inherent in the stated meaning, are used to mean a numerical value or a approximation thereof, and are used precisely to aid in the understanding of the present invention, or to prevent unscrupulous infringers from unfairly exploiting the disclosure in which an absolute numerical value is stated.
[0022] The present invention provides an ultra-high strength spring wire rod, steel wire, and a manufacturing method thereof, which are capable of ensuring high strength and excellent area reduction with little material deviation after IT heat treatment through optimization of the content of elements that promote segregation and a large reduction amount during continuous casting.
[0023] An ultra-high strength spring wire rod according to one embodiment of the present invention contains, by weight%, C: 0.5-0.7%, Si: 0.4-0.9%, Mn: 0.3-0.8%, Cr: 0.2-0.6%, P: 0.015% or less, S: 0.010% or less, Al: 0.01% or less, N: 0.01% or less, O: 0.005% or less, with the balance being Fe and unavoidable impurities.
[0024] The reasons for limiting the alloy composition of the ultra-high strength spring steel wire will be specifically described below. The reasons for limiting the alloy composition of the ultra-high strength spring steel wire are the same as those for the wire rod, so they will be omitted for the sake of brevity.
[0025] The C content is 0.5 to 0.7% by weight. C is an element added to ensure the strength of the product. If the C content is less than 0.5% by weight, the desired strength and Ceq cannot be ensured. As a result, the martensite structure is not completely formed when the steel is cooled, making it difficult to ensure the strength, and even if a complete martensite structure is formed, it is difficult to ensure the desired strength. If the C content exceeds 0.7% by weight, the impact properties are reduced and quenching cracks may occur during water cooling.
[0026] The Si content is 0.4 to 0.9% by weight. Silicon is used for deoxidizing steel and is an element advantageous in ensuring strength through solid solution strengthening. In order to ensure strength, silicon may be added in an amount of 0.4% by weight or more in the present invention. However, if excessive silicon is added, it may segregate in the center, causing a difference in hardness between the center and the surface layer, and may cause surface decarburization, which may make it difficult to process the material. In consideration of this, the upper limit of the silicon content in the present invention may be limited to 0.9% by weight.
[0027] The Mn content is 0.3 to 0.8% by weight. Mn is an element that improves hardening ability, and is one of the essential elements for forming high-strength tempered martensite structure steel. In order to ensure strength, manganese may be added in an amount of 0.3% by weight or more in the present invention. However, if Mn is added in excess, it segregates in the center, inducing a difference in hardness between the center and the surface layer, and there is a risk that the toughness of tempered martensite structure steel will decrease. In consideration of this, the upper limit of the Mn content in the present invention can be limited to 0.8% by weight.
[0028] The Cr content is 0.2 to 0.6 wt %. Cr, together with Mn, is effective in improving hardenability and improves the strength of tempered martensite steel. For this reason, Cr may be added in an amount of 0.2% by weight or more in the present invention. However, since Cr, like Si and Mn, is an element that promotes segregation, excessive addition of Cr may cause hardness deviation due to segregation in the center. Taking this into consideration, the upper limit of the Cr content in the present invention may be limited to 0.6% by weight.
[0029] The P content is 0.015% by weight or less. Since P is an element that segregates at grain boundaries and reduces toughness and hydrogen delayed fracture resistance, it is preferable to eliminate it from steel materials as much as possible. In the present invention, the upper limit can be limited to 0.015% by weight.
[0030] The S content is 0.010% by weight or less. Like P, S segregates at grain boundaries to reduce toughness and forms MnS to reduce hydrogen delayed fracture resistance, so it is preferable to eliminate S from steel materials as much as possible. In the present invention, the upper limit can be limited to 0.010% by weight.
[0031] The Al content is 0.01% by weight or less. Al is a strong deoxidizing element and can remove oxygen from steel to increase cleanliness. However, when Al is added, it forms Al2O3 inclusions, which reduces fatigue resistance. For this reason, the upper limit of Al content in the present invention can be limited to 0.01% by weight.
[0032] The N content is 0.01% by weight or less. N has the problem of combining with Al or V in the steel to form coarse AlN or VN precipitates that do not dissolve during heat treatment, and therefore the upper limit of N content in the present invention can be limited to 0.01% by weight.
[0033] The O content is 0.005% by weight or less. O can combine with Al to form coarse inclusions, so in the present invention, the upper limit can be limited to 0.005% by weight.
[0034] The remaining component of the present invention is iron (Fe). However, in normal manufacturing processes, unintended impurities may be inevitably mixed in from raw materials or the surrounding environment, and it is not possible to exclude them. Since any technician in normal manufacturing processes would know about these impurities, the contents of all of them will not be mentioned in this specification.
[0035] In the present invention, the central segregation of the wire is controlled in order to secure high strength and excellent reduction in area after IT heat treatment. 2The ratio of the area that satisfies one or more of C>0.8%, Si>0.9%, Cr>0.8% and Mn>0.8% by weight may be 5% or less.
[0036] If the above-mentioned area ratio exceeds 5%, hardness deviation occurs in the cross section perpendicular to the length direction after IT heat treatment, and therefore material deviation occurs, making it impossible to secure a sufficient reduction in area at the target strength.
[0037] In addition, according to the present invention, the surface decarburization phenomenon can be suppressed by using a low Si alloy composition. According to one example, the thickness of the surface ferrite decarburized layer of the wire may be 1 μm or less. If the thickness of the surface ferrite decarburized layer exceeds 1 μm, there is a risk that an additional process such as a carburizing treatment will be required to ensure high strength.
[0038] The manufacturing method of the ultra-high strength spring wire rod according to the present invention will be described in detail below. The ultra-high strength spring wire rod according to one embodiment of the present invention is manufactured by continuously casting molten steel having the above-mentioned alloy composition to prepare a bloom, rolling the bloom into a steel billet, and then rolling into a wire rod. Each manufacturing step will be described below.
[0039] In the present invention, in order to minimize the central segregation of the wire rod, the step of continuous casting is controlled in addition to the above-mentioned control of the alloy composition. According to one example, the casting speed during continuous casting is set to 0.48 to 0.54 m / min, and the total reduction during continuous casting can be soft reduced to 15 to 35 mm. The amount of cooling water is appropriately adjusted so that solidification can be completed up to the point where the soft reduction is completed.
[0040] If the casting speed is too slow, solidification is completed before soft reduction, the ratio of the liquid phase to the solid phase is too low, and it is difficult to ensure the effect of removing segregation by soft reduction. On the other hand, if the casting speed is too fast, the ratio of the liquid phase to the solid phase is too high, and segregation is formed due to solidification shrinkage, which is not preferable. In consideration of this, according to one example of the present invention, the casting speed is controlled to 0.48 to 0.54 m / min.
[0041] If the total reduction amount during soft reduction is too small, it is difficult to ensure the effect of removing segregation by soft reduction. On the other hand, if it is too large, the above-mentioned effect becomes saturated and damage to the continuous casting equipment may occur. In consideration of this, according to one example of the present invention, the total reduction amount of soft reduction is controlled to 15 to 35 mm.
[0042] According to one embodiment of the present invention, the soft reduction may be performed by rolling at 4 mm or less for each roll, and the cumulative reduction amount may be 60% or more when the solidification fraction is 0.6 or more. The solidification fraction means the ratio of the weight of the solid phase molten steel to the weight of the entire molten steel.
[0043] The bloom prepared by the above-mentioned process can be rolled into a billet and then rolled into a wire rod.
[0044] The method for producing the ultra-high strength spring steel wire according to the present invention will be described in detail below. The ultra-high strength spring steel wire according to the present invention satisfies the above-mentioned alloy composition and has a central 1 mm 2 It is manufactured by drawing wire rods that satisfy one or more of the following criteria (weight percentage) of 5% or less: C>0.8%, Si>0.9%, Cr>0.8%, and Mn>0.8%, heating the wires, water-cooling them under high pressure, tempering them, and water-cooling them. Each manufacturing step is explained below.
[0045] The wire rod described above in the wire drawing step of the present invention can be drawn into a steel wire having a wire diameter of 16 mm or less so as to be applicable to a suspension spring for a motorcycle suspension.
[0046] Next, in order to perform the QT heat treatment on the drawn steel wire, in the heating step of the present invention, the drawn steel wire is heated to the quenching temperature of 900 to 1000°C within 10 seconds, and then maintained for 5 to 60 seconds to heat treat the structure of the steel wire to austenitize it. If the heating time to the target temperature of 900 to 1000°C exceeds 10 seconds, crystal grains grow and it is difficult to ensure the desired physical properties. If the maintenance time is less than 5 seconds, the pearlite structure may not transform into austenite, and if it exceeds 60 seconds, the crystal grains may become coarse.
[0047] In the present invention, the step of water cooling at high pressure is a step of transforming the main structure of the steel wire from austenite to martensite, and water cooling can be performed at a high pressure capable of removing the boiling film of the austenitized steel wire in the previous step. In this case, if the cooling is performed by oil cooling instead of water cooling, the desired strength cannot be ensured due to low Ceq. In addition, if the pressure is not high enough to remove the boiling film during water cooling, the possibility of quenching cracks increases, so it is preferable to perform high-pressure water cooling by spraying water from all sides at the highest possible pressure during water cooling.
[0048] In the present invention, the tempering step is a step of heating martensite, which is the main structure of the water-cooled steel wire, and tempering it to tempered martensite. The tempering step can be performed by heating to 400 to 500°C within 10 seconds and maintaining the temperature within 30 seconds. If the tempering temperature is less than 400°C, the toughness is not ensured, processing is difficult, and the risk of the product being damaged increases, and if it exceeds 500°C, the strength decreases, so the tempering temperature is limited to the above-mentioned temperature range. In addition, if the tempering temperature is not heated to the above-mentioned temperature range within 10 seconds, coarse carbides may be formed and the toughness may decrease, so it is preferable to rapidly heat the steel wire within 10 seconds.
[0049] In the present invention, the means for heating to the quenching temperature and the means for tempering utilize IT heat treatment so that rapid heating can be performed and the surface can be sufficiently hardened during the subsequent water cooling. The tempered steel wire is then water-cooled to room temperature to produce ultra-high strength spring steel wire.
[0050] An ultra-high strength spring steel wire according to one embodiment of the present invention contains, by weight, 0.5-0.7% C, 0.4-0.9% Si, 0.3-0.8% Mn, 0.2-0.6% Cr, 0.015% or less P, 0.010% or less S, 0.01% or less Al, 0.01% or less N, 0.01% or less O, with the balance being Fe and unavoidable impurities, contains 90% or more tempered martensite by area fraction, and has a 1mm 2 The ratio of the area that satisfies one or more of C>0.8%, Si>0.9%, Cr>0.8% and Mn>0.8% by weight may be 5% or less.
[0051] In addition, the ultra-high strength spring steel wire according to one embodiment of the present invention may have a hardness deviation of 25 Hv or less in a cross section perpendicular to the longitudinal direction, except for a region having a depth of 0.5 mm or less from the outermost surface. If the hardness deviation exceeds 25 Hv, a sufficient reduction in area cannot be ensured.
[0052] Moreover, the ultra-high strength spring steel wire according to one example of the present invention may have a tensile strength of 1750 to 2200 MPa and a reduction in area of 40% or more.
[0053] The present invention will be described in more detail with reference to the following examples. However, it should be noted that the following examples are intended to illustrate and explain the present invention in more detail, and are not intended to limit the scope of the present invention, since the scope of the present invention is determined by the matters described in the claims and matters that can be reasonably inferred from them.
[0054] {Example} Molten steel having the alloy composition shown in Table 1 below was cast into blooms at the casting speed and total reduction amount shown in Table 2, and then rolled into billets and wire rods to produce wire rods with a diameter of 9 mm.
[0055] The segregation area in Table 2 is the area measured at the center of the cross section perpendicular to the length of the wire. 2 The "C segregation area" in Table 2 is the area of the central 1 mm2 The area is the percentage of the area that satisfies C>0.8% by weight. The "Si segregation area" is the area of the central 1 mm 2 The area is the percentage of the area that satisfies Si>0.9 wt%. "Cr segregation area" is the area of the central 1 mm 2 The area is the percentage of the area that satisfies Cr>0.8% by weight. "Mn segregation area" is the area of 1 mm2 at the center of a cross section perpendicular to the longitudinal direction. 2 The area refers to the percentage of the area that satisfies Mn>0.8% by weight.
[0056] [Table 1]
[0057] [Table 2]
[0058] The wire rods in Table 1 were then manufactured into steel wires with a diameter of 8 mm, and heat-treated under the conditions shown in Table 3 below. The order of heat treatment was austenitizing heat treatment - high pressure water cooling - tempering - water cooling. The hardness deviation refers to the hardness deviation measured when the hardness is measured at 10 or more points in the remaining area excluding the area 0.5 mm deep from the outermost surface on a cross section perpendicular to the length direction.
[0059] [Table 3]
[0060] As shown in Tables 1, 2, and 3, in Examples 1 and 2, which satisfy the alloy composition and manufacturing conditions of the present invention, in a cross section perpendicular to the longitudinal direction after IT heat treatment, the hardness deviation in the remaining region excluding the region 0.5 mm deep or less from the outermost surface was 25 Hv or less, the tensile strength was 1750 to 2200 MPa, and the area reduction rate was 40% or more. On the other hand, in Comparative Example 1, the Si and Mn contents were high, and hardness deviation occurred due to central Si and Mn segregation, and the area reduction rate was 40% or less.
[0061] In Comparative Example 2, the Si content was low and the target tensile strength was not achieved.
[0062] In Comparative Example 3, the casting speed was too fast and the soft reduction was insufficient, causing center segregation, which resulted in a large hardness deviation and a cross-sectional area reduction rate of 40% or less.
[0063] Although exemplary embodiments of the present invention have been described above, the present invention is not limited thereto, and a person having ordinary knowledge in the art can understand that various changes and modifications are possible within the scope of the concept and scope of the claims described in this specification. [Industrial Applicability]
[0064] According to one embodiment of the present invention, it is possible to provide a high-quality ultra-high strength spring wire rod, steel wire, and a manufacturing method thereof that have little material deviation after IT heat treatment and can ensure high strength and a high area reduction rate.
Claims
1. The steel comprises, by weight percent, C: 0.5-0.7%, Si: 0.4-0.9%, Mn: 0.3-0.8%, Cr: 0.2-0.6%, P: 0.015% or less, S: 0.010% or less, Al: 0.01% or less, N: 0.01% or less, O: 0.005% or less, with the balance being Fe and unavoidable impurities; 1 mm at the center of the cross section perpendicular to the length direction 2 1. An ultra-high strength spring wire rod, characterized in that the ratio of an area satisfying one or more of C>0.8%, Si>0.9%, Cr>0.8% and Mn>0.8% by weight is 5% or less.
2. 2. The ultra-high strength spring wire rod according to claim 1, wherein the thickness of the surface ferrite decarburized layer is 1 μm or less.
3. a step of continuously casting a molten steel containing, by weight, 0.5 to 0.7% C, 0.4 to 0.9% Si, 0.3 to 0.8% Mn, 0.2 to 0.6% Cr, 0.015% or less P, 0.010% or less S, 0.01% or less Al, 0.01% or less N, 0.005% or less O, with the balance being Fe and unavoidable impurities, to prepare a bloom; and rolling the bloom into a billet and then into a wire rod. The method for producing an ultra-high strength spring wire rod, wherein in the continuous casting step, a casting speed is set to 0.48 to 0.54 m / min, and soft reduction is performed during the continuous casting with a total reduction amount of 15 to 35 mm.
4. The soft reduction is 4. The method for producing ultra-high strength spring wire rod according to claim 3, wherein rolling is performed by rolling at 4 mm or less for each rolling roll, and when the solidification fraction is 0.6 or more, a cumulative rolling reduction is performed so as to be 60% or more.
5. The steel comprises, by weight percent, C: 0.5-0.7%, Si: 0.4-0.9%, Mn: 0.3-0.8%, Cr: 0.2-0.6%, P: 0.015% or less, S: 0.010% or less, Al: 0.01% or less, N: 0.01% or less, O: 0.005% or less, with the balance being Fe and unavoidable impurities; The area fraction of tempered martensite is 90% or more, 1 mm at the center of the cross section perpendicular to the length direction 2 1. An ultra-high strength spring steel wire, characterized in that a ratio of an area satisfying one or more of C>0.8%, Si>0.9%, Cr>0.8% and Mn>0.8% by weight is 5% or less.
6. 6. The ultra-high strength spring steel wire according to claim 5, wherein a hardness deviation in a region excluding a region having a depth of 0.5 mm or less from the outermost surface in a cross section perpendicular to the longitudinal direction is 25 Hv or less.
7. 6. The ultra-high strength spring steel wire according to claim 5, wherein the tensile strength is 1750 to 2200 MPa and the area reduction rate is 40% or more.
8. A step of drawing the wire rod according to claim 1; Heating to 900-1000° C. within 10 seconds; a step of water cooling at high pressure; Heating to 400-500°C within 10 seconds and tempering; and water-cooling the steel wire.
Citation Information
Patent Citations
JP1973000313U
High-strength steel wire rod excellent in wiredrawability
JP1987256950A
Manufacture of steel for spring
JP1995185763A
Steel wire rod for spring, excellent in cold workability
JP1997310151A
Light rolling reduction method for slab in continuous casting
JP2009183977A